Rural history of roman catholicism in Limasawa - Talde, Daniel C. (Danyag :the UPV journal of humanities and social sciences, 1998)
"Centuries after the first Catholic mass in the Philippines was celebrated on March 31, 1521, there is no adequate historical material on the evolution of the Catholic religion in Limasawa. Based mainly on oral accounts by members of the Roman Catholic community and supplemented by written documents and other sources of information, this study depicts the dynamics of the collective experience of the people of Limasawa, who, in their own voices, articulate their participation in and eventual contribution to the religious history of Filipinos."